Pomoc finansowa ze środków Państwowego Funduszu Rehabilitacji Osób Niepełnosprawnych jako instrument wspierania przedsiębiorczości osób niepełnosprawnych - Koza, Andrzej (Financial help from state fund of rehabilitation of disabled persons as an Instrument of supporting the disabled persons enterprises, 2006)
Disabled persons show low professional activity. Therefore financial support of this social group must be purposeful and effective. The loans from the Slate Fund of Rehabilitation of Disabled Persons are a good instrument to start the economic activity of those persons. The other possibility is the Fund’s help in paying interest to banks for loans. Between 2000 and 2003 the Fund loaned 76 million zlotys to over 3000 persons.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 199-207